Wirtschaft ist Care ist radikale Demokratie - Tecklenburg, Feline (Dass die Welt wohnlich für alle wird. Klartexte, Anfragen, Perspektiven. Ina Praetorius zum 65. Geburtstag)

Integrating human factors in the model based development of cyber-physical production systems - Gräßler, Iris; Wiechel, Dominik; Roesmann, Daniel (Procedia CIRP)
In order to optimize production processes and to avoid errors, it is not only necessary to automate processes, but also to integrate workers with their individual personality and skill profiles. For this purpose, human factors should be considered in the entire design process. The integrated view of mental human models, the cognitive demand of the working environment and the automation design is essential. Human-System Integration (HSI) constitutes a promising approach. Current model-based approaches offer possibilities to analyze and optimize tasks within an overall system, but they still lack integration. This leads to the research question: How can human factors be integrated into a system model of a socio-technical, Cyber-Physical Production System? The paper at hand contributes an approach of human factor integration into the procedure of Model-Based Systems Engineering for Cyber-Physical Production Systems (CPPS). The approach combines a system model of a CPPS with HSI concepts. In accordance to the benefits of MBSE, SysML is selected to integrate human factors in the development process of a CPPS. The approach is divided into five steps, which includes the extension of the SysML meta model. This allows the optimization of skill-based human-machine interaction. Defined HSI-Profiles enable system developers to integrate employee requirements at early stages within the development process. The approach is demonstrated by the maintenance of a 3D-Printer as a case example. This research enables system developers to depict individual workers with the help of the developed concepts and systematically integrate them into the development process of a CPPS.

Effectiveness of health-oriented leadership interventions for improving health and wellbeing of employees: a systematic review - Dannheim, Indra; Ludwig-Walz, Helena; Buyken, Anette; Grimm, Valerie; Kroke, Anja (Journal of Public Health)
Abstract Aim To identify and summarize the evidence for the effect of health-oriented leadership interventions on health and well-being outcomes at the employee level following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement (Moher et al. 2009). Subject and Methods A systematic search of relevant studies was conducted in multiple databases. Randomized controlled trials (RCTs), cluster-randomized controlled trials (cRCTs) and controlled before–after studies (CBAs) were included based on the following criteria: interventions that addressed supervisors, to raise awareness for the importance of health issues, teach mindfulness practices for conscious awareness, reduce stress and promote resources at the level of individual behavior, and evaluated the effect on at least one outcome of psychomental stress, absenteeism and well-being on the employee level. Results Of 6126 publications retrieved, ten studies were identified for analysis. Significant effects of leadership training were reported on exhaustion tendency, self-reported sickness absence, work-related sickness absence and job satisfaction in studies comparing health-oriented training programs to no intervention. Studies comparing health-oriented leadership training to other training did not report significant effects. Risk of bias was judged to be high in seven studies and unclear in three studies. Conclusion Evidence for the effectiveness of health-oriented leadership interventions on employees’ stress, absenteeism or well-being is judged to be low, clearly indicating the need for more and higher-quality research.
Keywords: Public Health; Environmental and Occupational Health

Evaluating the Design Space for Offloading 3D FFT Calculations to an FPGA for High-Performance Computing - Ramaswami, Arjun; Kenter, Tobias; Kühne, Thomas; Plessl, Christian (Applied Reconfigurable Computing. Architectures, Tools, and Applications)

Potassium Ion Conductivity in the Cubic Labyrinth of a Piezoelectric, Antiferromagnetic Oxoferrate(III) Tellurate(VI) - Albrecht, Ralf; Hoelzel, Markus; Beccard, Henrik; Rüsing, Michael; Eng, Lukas; Doert, Thomas; Ruck, Michael (Chemistry – A European Journal)
Orange-colored crystals of the oxoferrate tellurate K12+6xFe6Te4−xO27 [x=0.222(4)] were synthesized in a potassium hydroxide hydroflux with a molar water–base ratio n(H2O)/n(KOH) of 1.5 starting from Fe(NO3)3 ⋅ 9H2O, TeO2 and H2O2 at about 200 °C. By using (NH4)2TeO4 instead of TeO2, a fine powder consisting of microcrystalline spheres of K12+6xFe6Te4−xO27 was obtained. K12+6xFe6Te4−xO27 crystallizes in the acentric cubic space group Iurn:x-wiley:09476539:media:chem202102464:chem202102464-math-0001 3d. [FeIIIO5] pyramids share their apical atoms in [Fe2O9] groups and two of their edges with [TeVIO6] octahedra to form an open framework that consists of two loosely connected, but not interpenetrating, chiral networks. The flexibility of the hinged oxometalate network manifests in a piezoelectric response similar to that of LiNbO3.The potassium cations are mobile in channels that run along the <111> directions and cross in cavities acting as nodes. The ion conductivity of cold-pressed pellets of ball-milled K12+6xFe6Te4−xO27 is 2.3×10^(−4) S ⋅ cm^(−1) at room temperature. Magnetization measurements and neutron diffraction indicate antiferromagnetic coupling in the [Fe2O9] groups.
Keywords: General Chemistry; Catalysis; Organic Chemistry

A Method for Characterization of Geometric Deviations in Clinch Points with Computed Tomography and Transient Dynamic Analysis - Köhler, Daniel; Sadeghian, Behdad; Kupfer, Robert; Troschitz, Juliane; Gude, Maik; Brosius, Alexander (Key Engineering Materials)
When joining lightweight parts of various materials, clinching is a cost efficient solution. In a production line, the quality of a clinch point is primarily controlled by measurement of dimensions, which are accessible from outside. However, methods such as visual testing and measuring the bottom thickness as well as the outer diameter are not able to deliver any information about the most significant geometrical characteristic of the clinch point, neck thickness and undercut. Furthermore, ex-situ destructive methods such as microsectioning cannot detect elastic deformations and cracks that close after unloading. In order to exceed the current limits, a new non-destructive in-situ testing method for the clinching process is necessary. This work proposes a concept to characterize clinch points in-situ by combining two complementary non-destructive methods, namely, computed tomography (CT) and ultrasonic testing. Firstly, clinch points with different geometrical characteristics are analysed experimentally using ex-situ CT to get a highly spatially resolved 3D-image of the object. In this context, highly X-ray attenuating materials enhancing the visibility of the sheet-sheet interface are investigated. Secondly, the test specimens are modelled using finite element method (FEM) and a transient dynamic analysis (TDA) is conducted to study the effect of the geometrical differences on the deformation energy and to qualify the TDA as a fast in-situ non-destructive method for characterizing clinch points at high temporal resolution.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Characterization of Liquid-Phase Distribution in 3D Printed Structured Packings with an Enclosed Column Wall - Reitze, Arnulf; Grünewald, Marcus; Riese, Julia (Industrial & Engineering Chemistry Research)
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Entwicklungssystematik zur Integration von Eigenschaften der Selbstheilung in Intelligente Technische Systeme - Hillebrand, Michael

3D-Geometrie–virtuell und real - Biehler, Rolf; Weigand, Hans-Georg (mathematik lehren)

Schatten von 3D-Objekten: Modellierung mit GeoGebra 3D und Anwendungen in der Computergrafik - Höper, Lukas; Malin, Leah; Biehler, Rolf (mathematik lehren)

Faszination 3D-Film: Entwicklung einer 3D-Konstruktion - Hüsing, Sven; Weiser, Niklas; Biehler, Rolf (mathematik lehren)

Tire Wear Reduction Based on an Extended Multibody Rear Axle Model - Schütte, Jan; Sextro, Walter (Vehicles)
To analyze the influence of suspension kinematics on tire wear, detailed simulation models are required. In this study, a non-linear, flexible multibody model of a rear axle system is built up in the simulation software MSC Adams/View. The physical model comprises the suspension kinematics, compliance, and dynamics as well as the non-linear behavior of the tire using the FTire model. FTire is chosen because it has a separate tire tread model to compute the contact pressure and friction force distribution in the tire contact patch. To build up the simulation model, a large amount of data is needed. Bushings, spring, and damper characteristics are modeled based on measurements. For the structural components (e.g., control arms), reverse engineering techniques are used. The components are 3D-scanned, reworked, and included as a modal reduced finite element (FE)-model using component mode synthesis by Craig–Bampton. Finally, the suspension model is validated by comparing the simulated kinematic and compliance characteristics to experimental results. To investigate the interaction of suspension kinematics and tire wear, straight line driving events, such as acceleration, driving with constant velocity, and deceleration, are simulated with different setups of wheel suspension kinematics. The influence of the setups on the resulting friction work between tire and road is examined, and an exemplarily calculation of tire wear based on a validated FTire tire model is carried out. The results demonstrate, on the one hand, that the chosen concept of elasto-kinematic axle leads to a relatively good match with experimental results and, on the other hand, that there are significant possibilities to reduce tire wear by adjusting the suspension kinematics.

Autoethnografie und Kreatives Schreiben - Vochatzer, Stefanie; Engelmann , Sebastian (Journal der Schreibwissenschaft)

ProConAR: A Tool Support for Model-based AR Product Configuration - Gottschalk, Sebastian; Yigitbas, Enes; Schmidt, Eugen; Engels, Gregor (Human-Centered Software Engineering. HCSE 2020)
Mobile shopping apps have been using Augmented Reality (AR) in the last years to place their products in the environment of the customer. While this is possible with atomic 3D objects, there is is still a lack in the runtime conﬁguration of 3D object compositions based on user needs and environmental constraints. For this, we previously developed an approach for model-based AR-assisted product conﬁguration based on the concept of Dynamic Software Product Lines. In this demonstration paper, we present the corresponding tool support ProConAR in the form of a Product Modeler and a Product Conﬁgurator. While the Product Modeler is an Angular web app that splits products (e.g. table) up into atomic parts (e.g. tabletop, table legs, funnier) and saves it within a conﬁguration model, the Product Conﬁgurator is an Android client that uses the conﬁguration model to place diﬀerent product conﬁgurations within the environment of the customer. We show technical details of our ready to use tool-chain ProConAR by describing its implementation and usage as well as pointing out future research directions.
Keywords: Product Configuration; Augmented Reality; Model-based; Tool Support

Nonlinear dielectric properties of random paraelectric-dielectric composites - Myroshnychenko, Viktor; Smirnov, Stanislav; Jose, Pious Mathews Mulavarickal; Brosseau, Christian; Förstner, Jens (Acta Materialia)
The challenge of designing new tunable nonlinear dielectric materials with tailored properties has attracted an increasing amount of interest recently. Herein, we study the effective nonlinear dielectric response of a stochastic paraelectric-dielectric composite consisting of equilibrium distributions of circular and partially penetrable disks (or parallel, infinitely long, identical, partially penetrable, circular cylinders) of a dielectric phase randomly dispersed in a continuous matrix of a paraelectric phase. The random microstructures were generated using the Metropolis Monte Carlo algorithm. The evaluation of the effective permittivity and tunability were carried out by employing either a Landau thermodynamic model or its Johnson’s approximation to describe the field-dependent permittivity of the paraelectric phase and solving continuum-electrostatics equations using finite element calculations. We reveal that the percolation threshold in this composite governs the critical behavior of the effective permittivity and tunability. For microstructures below the percolation threshold, our simulations demonstrate a strong nonlinear behaviour of the field-dependent effective permittivity and very high tunability that increases as a function of dielectric phase concentration. Above the percolation threshold, the effective permittivity shows the tendency to linearization and the tunability dramatically drops down. The highly reduced permittivity and extraordinarily high tunability are obtained for the composites with dielectric impenetrable disks at high concentrations, in which the triggering of the percolation transition is avoided. The reported results cast light on distinct nonlinear behaviour of 2D and 3D stochastic composites and can guide the design of novel composites with the controlled morphology and tailored permittivity and tunability.

Tests and Proofs - 14th International Conference, TAP@STAF 2020, Bergen, Norway, June 22-23, 2020, Proceedings [postponed]

Mapping postprandial responses sets the scene for targeted dietary advice - Brand-Miller, Jennie; Buyken, Anette (Nature Medicine)

Additiveteile Direktverschrauben - Moritzer, Elmar; Hillemeyer, Johannes (6. Fachkonferenz 3D-Druck in der Automobielindustrie)

Wechseldehnungsschweißen - Entwicklung einer Fügetechnologie für 3D-Geometrien - Vogtschmidt, Sascha; Fiebig, Isabel; Schöppner, Volker (Joining Plastics)

Wechseldehnungsschweißen - Entwicklung einer Fügetechnologie für 3D-Geometrien - Vogtschmidt, Sascha; Schöppner, Volker (DVS CONGRESS 2020 - Große Schweißtechnische Tagung)

From filament production to material qualification for the FDM process - Moritzer, Elmar; Wächter, Julian

Long‐term effects of hydrolyzed formulae on atopic diseases in the GINI study - Gappa, Monika; Filipiak‐Pittroff, Birgit; Libuda, Lars; Berg, Andrea; Koletzko, Sibylle; Bauer, Carl‐Peter; Heinrich, Joachim; Schikowski, Tamara; Berdel, Dietrich; Standl, Marie (Allergy)

A mendelian randomization study on causal effects of 25(OH)vitamin D levels on attention deficit/hyperactivity disorder - Libuda, Lars; Naaresh, Roaa; Ludwig, Christine; Laabs, Björn-Hergen; Antel, Jochen; Föcker, Manuel; Hebebrand, Johannes; Hinney, Anke; Peters, Triinu (European Journal of Nutrition)
Abstract Background While observational studies revealed an inverse association between serum 25(OH)vitamin D (25(OH)D) and the risk of attention deficit/hyperactivity disorder (ADHD), the causality of this relationship remains unclear. Methods We conducted a bidirectional two-sample Mendelian Randomization (MR) study to examine whether 25(OH)D has an effect on the risk to develop ADHD or vice versa. Information on single nucleotide polymorphisms (SNP) associated with serum 25(OH)D was obtained from a genome-wide association study (GWAS) considering phenotype data from 79,366 individuals of European ancestry. Data on risk for ADHD were derived from a GWAS analysis with 20,183 individuals diagnosed with ADHD and 35,191 controls. For our analysis, we considered effect sizes based on the European participants (19,099 cases and 34,194 controls). Results Single SNP analyses showed a causal effect of vitamin D on ADHD risk for only one SNP (rs12785878, p = 0.024). The overall MR estimates did not reveal a causal effect of 25(OH)D on risk for ADHD. In the reverse analysis, neither any single nor the multi-SNP MR analyses showed a causal effect of ADHD on 25(OH)D. Conclusion Results from this two-sample MR study did not confirm a causal effect of 25(OH)D on ADHD or vice versa. Accordingly, our study does not provide evidence that improving 25(OH)D via supplementation could reduce the risk of developing ADHD.

The overall diet quality in childhood is prospectively associated with the timing of puberty - Duan, Ruonan; Qiao, Tian; Chen, Yue; Chen, Mengxue; Xue, Hongmei; Zhou, Xue; Yang, Mingzhe; Liu, Yan; Zhao, Li; Libuda, Lars; Cheng, Guo (European Journal of Nutrition)
Abstract Purpose The influences of nutrition in childhood on puberty onset could have sustained consequences for health and wellbeing later in life. The aim of this study was to investigate the prospective association of diet quality prior to puberty with the timing of puberty onset. Methods We considered data from 3983 SCCNG (Southwest China Childhood Nutrition and Growth) study participants with dietary data, anthropometric measurement, and information on potential confounders at their baseline assessment (mean age: 7.1 years for girls and 7.3 years for boys; mean length of follow-up was 4.2 years). Cox proportional hazard regression estimating hazard ratios (HRs) and 95% confidence intervals (CIs) were used to examine the relationship between diet quality and puberty onset. Dietary intake at baseline was assessed using a validated food frequency questionnaire. Diet quality was determined using the Chinese Children Dietary Index (CCDI) which measures adherence to current dietary recommendations (theoretical range: 0–160 points). Age at Tanner stage 2 for breast/genital development (B2/G2), menarche or voice break (M/VB) were used as pubertal markers. Results The CCDI score ranged from 56.2 to 136.3 for girls and 46.1–131.5 for boys. Pubertal markers consistently indicate that girls and boys with higher diet quality were more likely to enter their puberty later than their counterparts with lower CCDI scores (higher vs. lower CCDI tertiles: adjusted HR for age at B2: 0.85 (95% CI, 0.81–0.94), p for trend = 0.02; G2: 0.86 (95% CI,0.80–0.96), p for trend = 0.02; M: 0.86 (95% CI,0.80–0.95), p for trend = 0.02; VB: 0.86 (95% CI,0.79–0.98), p for trend = 0.03), after adjustment for paternal education level, baseline energy intake, and pre-pubertal body fat. Conclusions Our data suggested a later puberty onset and later timing of progressed puberty stages in children with a high diet quality, which were independent of pre-pubertal body fat.

Die Ernährungsversorgung in Familien zwischen Zeit, Alltag und Haushaltsführung. Eine Mixed-Methods-Untersuchung - Klünder, Nina

Der Jugendamts-Monitor. Aufgaben – Trends – Daten - Müller, Heinz; Klünder, Nina

Dietary flavonoids among children and adolescents in the Dortmund Nutritional and Anthropometric Longitudinally Designed (DONALD) study: intake, food sources and trends from 1985 until 2016 - Rienks, Johanna; Penczynski, Katharina J.; Schmitting, Sarah; Buyken, Anette; Nöthlings, Ute (British Journal of Nutrition)
Abstract Flavonoids are suggested to reduce disease risk. Since dietary habits are acquired during early life, describing age and time trends of flavonoid intake and major food sources are important for monitoring and disease prevention in later life. We aimed to describe total flavonoid intake and food sources and to investigate age and time trends of flavonoid intake in 3–18-year-olds, from the Dortmund Nutritional and Anthropometric Longitudinally Designed study from 1985 to 2016. Intake was assessed annually using 3-d weighed food records (WFR). Flavonoid values were assigned using the United States Department of Agriculture database. Foods contributing to intake were determined. Age and time trends in total flavonoid and isoflavone density were analysed by sex with PROC MIXED. In total, 1312 children completed 10 758 WFR. Across all ages, daily mean total flavonoid density was lower in boys compared with girls (134 v . 146 mg/4184 kJ) and no difference in median isoflavone density (0·04 mg/4184 kJ per d) was found. The top five foods contributing to total flavonoid intake were apple with peel (15·0/17·1 %), strawberries (5·9/6·1 %), chocolate spread (3·9/3·5 %), orange juice (3·5/3·4 %) and pasta (3·5/3·4 %) for boys and girls, respectively. Overall, in boys, total flavonoid density decreased over the course of age and time. In girls, there was no association with age or time. In both sexes, isoflavone density followed a U-shaped age trend with no change over time. From a public health perspective, the overall observed downwards trend of flavonoid intake in boys deserves attention. Future initiatives should be tailored at maintaining a high flavonoid density as children age, specifically among boys.

Short-term metreleptin treatment of patients with anorexia nervosa: rapid on-set of beneficial cognitive, emotional, and behavioral effects - Milos, Gabriella; Antel, Jochen; Kaufmann, Lisa-Katrin; Barth, Nikolaus; Koller, Antonia; Tan, Susanne; Wiesing, Urban; Hinney, Anke; Libuda, Lars; Wabitsch, Martin; von Känel, Roland; Hebebrand, Johannes (Translational Psychiatry)
Abstract To examine the hypothesis that normalization of low circulating leptin levels in patients with anorexia nervosa ameliorates hyperactivity, three seriously ill females with hyperactivity were treated off-label with metreleptin (recombinant human leptin) for up to 14 days. Drive for activity, repetitive thoughts of food, inner restlessness, and weight phobia decreased in two patients. Surprisingly, depression improved rapidly in all patients. No serious adverse events occurred. Due to obvious limitations of uncontrolled case series, placebo-controlled clinical trials are mandatory to confirm the observed rapid onset of beneficial effects. Our findings suggest an important role of hypoleptinemia in the mental and behavioral phenotype of anorexia nervosa.

The Role of Genetic Variation of BMI, Body Composition, and Fat Distribution for Mental Traits and Disorders: A Look-Up and Mendelian Randomization Study - Peters, Triinu; Nüllig, Lena; Antel, Jochen; Naaresh, Roaa; Laabs, Björn-Hergen; Tegeler, Lisa; Amhaouach, Chaima; Libuda, Lars; Hinney, Anke; Hebebrand, Johannes (Frontiers in Genetics)

Early changes in hepatic energy metabolism and lipid content in recent-onset type 1 and 2 diabetes mellitus - Kupriyanova, Yuliya; Zaharia, Oana Patricia; Bobrov, Pavel; Karusheva, Yanislava; Burkart, Volker; Szendroedi, Julia; Hwang, Jong-Hee; Roden, Michael; Roden, M.; Al-Hasani, H.; Burkart, V.; Buyken, Anette; et al. (Journal of Hepatology)

World trends in sugar-sweetened beverage and dietary sugar intakes in children and adolescents: a systematic review - Della Corte, Karen; Fife, Jessica; Gardner, Alexis; Murphy, Britta L; Kleis, Linda; Della Corte, Dennis; Schwingshackl, Lukas; LeCheminant, James D; Buyken, Anette (Nutrition Reviews)
Abstract Objective To provide a systematic overview of world dietary sugar and sugar-sweetened beverage (SSB) intake trends in children and adolescents. Data Sources Medline, Embase, and the Cochrane Central Register of Controlled Trials in the Cochrane Library were searched through January 2019 to identify longitudinal follow-up studies with time-trend data and repeated cross-sectional studies. Data Extraction Data from studies reporting ≥ 2 measurements (sugars, SSB, or sweets/candy) over ≥ 2 years and included ≥ 20 healthy, normal- or overweight children or adolescents aged 1–19 years. Data Analysis Data from 43 articles (n = 4 prospective cohort studies; n = 39 repeated cross-sectional studies) from 15 countries (n = 8 European countries plus Australia, Canada, China, South Korea, Mexico, Russia, and the United States) are presented narratively. According to the risk of bias in nonrandomized studies of interventions tool, 34 studies were judged to have a moderate risk of bias, and 5 to have a serious risk of bias. Conclusions Consumption among US children and adolescents increased substantially in the decades preceding 2000, followed by a faster and continued decline. As a whole, other international intake trends did not reveal drastic increases and decreases in SSB and dietary sugars; they tended to change only slightly across 3 decades.

Dietary Fibre Consensus from the International Carbohydrate Quality Consortium (ICQC) - Augustin, Livia S. A.; Aas, Anne-Marie; Astrup, Arnie; Atkinson, Fiona S.; Baer-Sinnott, Sara; Barclay, Alan W.; Brand-Miller, Jennie C.; Brighenti, Furio; Bullo, Monica; Buyken, Anette; Ceriello, Antonio; Ellis, Peter R.; et al. (Nutrients)
Dietary fibre is a generic term describing non-absorbed plant carbohydrates and small amounts of associated non-carbohydrate components. The main contributors of fibre to the diet are the cell walls of plant tissues, which are supramolecular polymer networks containing variable proportions of cellulose, hemicelluloses, pectic substances, and non-carbohydrate components, such as lignin. Other contributors of fibre are the intracellular storage oligosaccharides, such as fructans. A distinction needs to be made between intrinsic sources of dietary fibre and purified forms of fibre, given that the three-dimensional matrix of the plant cell wall confers benefits beyond fibre isolates. Movement through the digestive tract modifies the cell wall structure and may affect the interactions with the colonic microbes (e.g., small intestinally non-absorbed carbohydrates are broken down by bacteria to short-chain fatty acids, absorbed by colonocytes). These aspects, combined with the fibre associated components (e.g., micronutrients, polyphenols, phytosterols, and phytoestrogens), may contribute to the health outcomes seen with the consumption of dietary fibre. Therefore, where possible, processing should minimise the degradation of the plant cell wall structures to preserve some of its benefits. Food labelling should include dietary fibre values and distinguish between intrinsic and added fibre. Labelling may also help achieve the recommended intake of 14 g/1000 kcal/day.

Inflammatory mediators in the adipo-renal axis: leptin, adiponectin, and soluble ICAM-1 - Hua, Yifan; Herder, Christian; Kalhoff, Hermann; Buyken, Anette; Esche, Jonas; Krupp, Danika; Wudy, Stefan A.; Remer, Thomas (American Journal of Physiology-Renal Physiology)
A lower 24-h urine pH (24h-pH), i.e., a higher renal excretion of free protons, at a given acid load to the body, denotes a reduction in the kidney’s capacity for net acid excretion (NAE). There is increasing evidence, not only for patients with type 2 diabetes but also for healthy individuals, that higher body fatness or waist circumference (WC) has a negative impact on renal function to excrete acids (NAE). We hypothesized that adiposity-related inflammation molecules might mediate this relation between adiposity and renal acid excretion function. Twelve biomarkers of inflammation were measured in fasting blood samples from 162 adult participants (18–25 yr old) of the Dortmund Nutritional and Anthropometric Longitudinally Designed (DONALD) study who had undergone anthropometric measurements and collected 24-h urine samples. Both Baron and Kenny’s (B&K’s) steps to test mediation and causal mediation analysis were conducted to examine the potential mediatory roles of biomarkers of inflammation in the WC-24-h pH relationship after strictly controlling for laboratory-measured NAE. In B&K’s mediation analysis, leptin, soluble intercellular adhesion molecule 1 (sICAM-1), and adiponectin significantly associated with the outcome 24-h pH and attenuated the WC-pH relation. In agreement herewith, causal mediation analysis estimated the “natural indirect effects” of WC on 24-h pH via leptin ( P = 0.01) and adiponectin ( P = 0.03) to be significant, with a trend for sICAM-1 ( P = 0.09). The calculated proportions mediated by leptin, adiponectin, and sICAM-1 were 64%, 23%, and 12%, respectively. Both mediation analyses identified an inflammatory cytokine (leptin) and an anti-inflammatory cytokine (adiponectin) along with sICAM-1 as being potentially involved in mediating adiposity-related influences on renal acid excretion capacity.

Early life factors and their relevance to intima-media thickness of the common carotid artery in early adulthood - Nyasordzi, Juliana; Penczynski, Katharina; Remer, Thomas; Buyken, Anette (PLOS ONE)

Reply to Khan et al. - Schwingshackl, Lukas; Neuenschwander, Manuela; Hoffmann, Georg; Buyken, Anette; Schlesinger, Sabrina (The American Journal of Clinical Nutrition)

Sugar intake among German adolescents: trends from 1990 to 2016 based on biomarker excretion in 24-h urine samples - Perrar, Ines; Gray, Nicola; Kuhnle, Gunter G.; Remer, Thomas; Buyken, Anette; Alexy, Ute (British Journal of Nutrition)
Abstract Trend analyses based on dietary records suggest decreases in the intakes of total sugar (TS), added and free sugar since 2005 among children and adolescents in Germany. In terms of age trends, TS intake decreased with increasing age. However, self-reported sugar intake in epidemiological studies is criticised, as it may be prone to bias due to selective underreporting. Furthermore, adolescents are more susceptible to underreporting than children. We thus analysed time and age trends in urinary fructose excretion (FE), sucrose excretion (SE) and the sum of both (FE + SE) as biomarkers for sugar intake among 8·5–16·5-year-old adolescents. Urinary sugar excretion was measured by UPLC-MS/MS in 997 24-h urine samples collected from 239 boys and 253 girls participating in the Dortmund Nutritional and Anthropometric Longitudinally Designed (DONALD) study cohort between 1990 and 2016. Time and age trends of log-transformed FE, SE and FE + SE were analysed using polynomial mixed-effects regression models. Between 1990 and 2016, FE as well as FE + SE decreased (linear time trend: P = 0·0272 and P < 0·0001, respectively). A minor increase in excretion during adolescence was confined to FE (linear age trend: P = 0·0017). The present 24-h excretion measurements support a previously reported dietary record-based decline in sugar intake since 2005. However, the previously seen dietary record-based decrease in TS from childhood to late adolescence was not confirmed by our biomarker analysis, suggesting a constant sugar intake for the period of adolescence.

The Relationship between Glycemic Index and Health - Brand-Miller, Jennie; Buyken, Anette (Nutrients)
There is no question that elevated postprandial glycemia is a significant driver of common chronic diseases globally [...]

Tests and Proofs - 14th International Conference, TAP@STAF 2020, Bergen, Norway, June 22-23, 2020, Proceedings [postponed]

NFDI4Culture - Consortium for research data on material and immaterial cultural heritage - Altenhöner, Reinhard; Blümel, Ina; Boehm, Franziska; Bove, Jens; Bicher, Katrin; Bracht, Christian; Brand, Ortrun; Dieckmann, Lisa; Effinger, Maria; Hagener, Malte; Hammes, Andrea; Heller, Lambert; et al. (Research Ideas and Outcomes)
Digital data on tangible and intangible cultural assets is an essential part of daily life, communication and experience. It has a lasting influence on the perception of cultural identity as well as on the interactions between research, the cultural economy and society. Throughout the last three decades, many cultural heritage institutions have contributed a wealth of digital representations of cultural assets (2D digital reproductions of paintings, sheet music, 3D digital models of sculptures, monuments, rooms, buildings), audio-visual data (music, film, stage performances), and procedural research data such as encoding and annotation formats. The long-term preservation and FAIR availability of research data from the cultural heritage domain is fundamentally important, not only for future academic success in the humanities but also for the cultural identity of individuals and society as a whole. Up to now, no coordinated effort for professional research data management on a national level exists in Germany. NFDI4Culture aims to fill this gap and create a user-centered, research-driven infrastructure that will cover a broad range of research domains from musicology, art history and architecture to performance, theatre, film, and media studies. The research landscape addressed by the consortium is characterized by strong institutional differentiation. Research units in the consortium's community of interest comprise university institutes, art colleges, academies, galleries, libraries, archives and museums. This diverse landscape is also characterized by an abundance of research objects, methodologies and a great potential for data-driven research. In a unique effort carried out by the applicant and co-applicants of this proposal and ten academic societies, this community is interconnected for the first time through a federated approach that is ideally suited to the needs of the participating researchers. To promote collaboration within the NFDI, to share knowledge and technology and to provide extensive support for its users have been the guiding principles of the consortium from the beginning and will be at the heart of all workflows and decision-making processes. Thanks to these principles, NFDI4Culture has gathered strong support ranging from individual researchers to high-level cultural heritage organizations such as the UNESCO, the International Council of Museums, the Open Knowledge Foundation and Wikimedia. On this basis, NFDI4Culture will take innovative measures that promote a cultural change towards a more reflective and sustainable handling of research data and at the same time boost qualification and professionalization in data-driven research in the domain of cultural heritage. This will create a long-lasting impact on science, cultural economy and society as a whole.

Method for 3D-Environment Driven Domain Knowledge Elicitaion and System Model Generation - Japs, Segej; Kharatyan, Aschot; Tekaat, Julian; Kaiser, Lydia; Dumitrescu, Roman (Proceedings of the Design Society)

CONSENS 3D: Method for 3D-Environment Driven Domain Knowledge Elicitaion and System Model Generation - Japs, Segej; Kharatyan, Aschot; Kaiser, Lydia; Dumitrescu, Roman (Proceedings of the 16th International Design Conference (DESIGN 2020))

Opportunities of 3D Machine Learning for Manufacturability Analysis and Component Recognition in the Additive Manufacturing Process Chain - Nickchen, Tobias; Engels, Gregor; Lohn, Johannes (Industrializing Additive Manufacturing)

Vorhersage der Rissinitiierung in 3D-Strukturen mit ADAPCRACK3D - Joy, Tintu David; Kullmer, Gunter; Risse, Lena

Light diffraction in slab waveguide lenses simulated with the stepwise angular spectrum method - Ebers, Lena; Hammer, Manfred; Förstner, Jens (Optics Express)
A stepwise angular spectrum method (SASM) for curved interfaces is presented to calculate the wave propagation in planar lens-like integrated optical structures based on photonic slab waveguides. The method is derived and illustrated for an effective 2D setup first and then for 3D slab waveguide lenses. We employ slab waveguides of different thicknesses connected by curved surfaces to realize a lens-like structure. To simulate the wave propagation in 3D including reflection and scattering losses, the stepwise angular spectrum method is combined with full vectorial finite element computations for subproblems with lower complexity. Our SASM results show excellent agreement with rigorous numerical simulations of the full structures with a substantially lower computational effort and can be utilized for the simulation-based design and optimization of complex and large scale setups.
Keywords: tet_topic_waveguides

A simplified method for the evaluation of the layer compression test using one 3D digital image correlation system and considering the material anisotropy by the equibiaxial Lankford parameter - Camberg, Alan Adam; Tröster, Thomas

Model-based Product Configuration in Augmented Reality Applications - Gottschalk, Sebastian; Yigitbas, Enes; Schmidt, Eugen; Engels, Gregor (Human-Centered Software Engineering. HCSE 2020)
Augmented Reality (AR) has recently found high attention in mobile shopping apps such as in domains like furniture or decoration. Here, the developers of the apps focus on the positioning of atomic 3D objects in the physical environment. With this focus, they neglect the conﬁguration of multi-faceted 3D object composition according to the user needs and environmental constraints. To tackle these challenges, we present a model-based approach to support AR-assisted product con-ﬁguration based on the concept of Dynamic Software Product Lines. Our approach splits products (e.g. table) into parts (e.g. tabletop, ta-ble legs, funnier) with their 3D objects and additional information (e.g. name, price). The possible products, which can be conﬁgured out of these parts, are stored in a feature model. At runtime, this feature model can be used to conﬁgure 3D object compositions out of the product parts and adapt to user needs and environmental constraints. The beneﬁts of this approach are demonstrated by a case study of conﬁguring modular kitchens with the help of a prototypical mobile-based implementation.
Keywords: Product Configuration; Augmented Reality; Runtime Adaptation; Dynamic Software Product Lines

Local Gathering of Mobile Robots in Three Dimensions - Braun, Michael; Castenow, Jannik; Meyer auf der Heide, Friedhelm (Proceedings of the 27th Conference on Structural Information and Communication Complexity (SIROCCO))
In this work, we initiate the research about the Gathering problem for robots with limited viewing range in the three-dimensional Euclidean space. In the Gathering problem, a set of initially scattered robots is required to gather at the same position. The robots' capabilities are very restricted -- they do not agree on any coordinate system or compass, have a limited viewing range, have no memory of the past and cannot communicate. We study the problem in two different time models, in FSYNC (fully synchronized discrete rounds) and the continuous time model. For FSYNC, we introduce the 3D-Go-To-The-Center-strategy and prove a runtime of $Θ(n^2)$ that matches the currently best runtime bound for the same model in the Euclidean plane [SPAA'11]. Our main result is the generalization of contracting strategies (continuous time) from [Algosensors'17] to three dimensions. In contracting strategies, every robot that is located on the global convex hull of all robots' positions moves with full speed towards the inside of the convex hull. We prove a runtime bound of $O(Δ · n^{3/2})$ for any three-dimensional contracting strategy, where $Δ$ denotes the diameter of the initial configuration. This comes up to a factor of $\sqrt{n}$ close to the lower bound of $Ω (Δ · n)$ which is already true in two dimensions. In general, it might be hard for robots with limited viewing range to decide whether they are located on the global convex hull and which movement maintains the connectivity of the swarm, rendering the design of concrete contracting strategies a challenging task. We prove that the continuous variant of 3D-Go-To-The-Center is contracting and keeps the swarm connected. Moreover, we give a simple design criterion for three-dimensional contracting strategies that maintains the connectivity of the swarm and introduce an exemplary strategy based on this criterion.

Distinguishing Knowledge Impact from Citation Impact: A Methodology for Analysing Knowledge Impact for the Literature Review Genre - Schryen, Guido; Wagner, Gerit; Benlian, Alexander
The scientific impact of research papers is multi-dimensional and can be determined quantitatively by means of citation analysis and qualitatively by means of content analysis. Accounting for the widely acknowledged limitations of pure citation analysis, we adopt a knowledge-based perspective on scientific impact to develop a methodology for content-based citation analysis which allows determining how papers have enabled knowledge development in subsequent research (knowledge impact). As knowledge development differs between research genres, we develop a new knowledgebased citation analysis methodology for the genre of standalone literature reviews (LRs). We apply the suggested methodology to the IS business value domain by manually coding 22 LRs and 1,228 citing papers (CPs) and show that the results challenge the assumption that citations indicate knowledge impact. We derive implications for distinguishing knowledge impact from citation impact in the LR genre. Finally, we develop recommendations for authors of LRs, scientific evaluation committees and editorial boards of journals how to apply and benefit from the suggested methodology, and we discuss its efficiency and automatization.
Keywords: Scientific impact; knowledge impact; content-based citation analysis; methodology

Structural Elements Regulating the Photochromicity in a Cyanobacteriochrome - Xu, Xiuling; Port, Astrid; Wiebeler, Christian; Zhao, Kai-Hong; Schapiro, Igor; Gärtner, Wolfgang (Proceedings of the National Academy of Sciences)
The three-dimensional (3D) crystal structures of the GAF3 domain of cyanobacteriochrome Slr1393 ( Synechocystis PCC6803) carrying a phycocyanobilin chromophore could be solved in both 15- Z dark-adapted state, Pr, λ max = 649 nm, and 15- E photoproduct, Pg, λ max = 536 nm (resolution, 1.6 and 1.86 Å, respectively). The structural data allowed identifying the large spectral shift of the Pr-to-Pg conversion as resulting from an out-of-plane rotation of the chromophore’s peripheral rings and an outward movement of a short helix formed from a formerly unstructured loop. In addition, a third structure (2.1-Å resolution) starting from the photoproduct crystals allowed identification of elements that regulate the absorption maxima. In this peculiar form, generated during X-ray exposition, protein and chromophore conformation still resemble the photoproduct state, except for the D-ring already in 15- Z configuration and tilted out of plane akin the dark state. Due to its formation from the photoproduct, it might be considered an early conformational change initiating the parental state-recovering photocycle. The high quality and the distinct features of the three forms allowed for applying quantum-chemical calculations in the framework of multiscale modeling to rationalize the absorption maxima changes. A systematic analysis of the PCB chromophore in the presence and absence of the protein environment showed that the direct electrostatic effect is negligible on the spectral tuning. However, the protein forces the outer pyrrole rings of the chromophore to deviate from coplanarity, which is identified as the dominating factor for the color regulation.

Evaluation of MMCs for High-Power Low-Voltage DC-Applications in Combination with the Module LLC-Design - Unruh, Roland; Schafmeister, Frank; Böcker, Joachim (2020 22nd European Conference on Power Electronics and Applications (EPE'20 ECCE Europe))
In this paper, a full-bridge modular multilevel converter (MMC) and two half-bridge-based MMCs are evaluated for high-current low-voltage e.g. 100 - 400V DC-applications such as electrolysis, arc welding or datacenters with DC-power distribution. Usually, modular multilevel converters are used in high-voltage DC-applications (HVDC) in the multiple kV-range, but to meet the needs of a high-current demand at low output voltage levels, the modular converter concept requires adaptations. In the proposed concept, the MMC is used to step-down the three-phase medium-voltage of 10kV, and provide up to 1 MW to the load. Therefore, each module is extended by an LLC resonant converter to adapt to the specific electrolyzers DC-voltage range of 142 - 220V and to provide galvanic isolation. The six-arm MMC converter with half-bridge modules can be simplified and optimized by removing three arms, and thus halving the number of modules. In addition, the module voltage ripple and capacitor losses are decreased by 22% and 30% respectively. By rearranging the components of the half-bridge MMC to build a MMC consisting of grid-side full-bridge modules, the voltage ripple is further reduced by 78% and capacitor losses by 64%, while ensuring identical costs and volume for all MMCs. Finally, the LLC resonant converter is designed for the most efficient full-bridge MMC. The LLC can not operate at resonance with a fixed nominal module voltage of 770V because the output voltage is varying between 142 - 220V. By decreasing the module voltage down to 600V, additional points of operation can be operated in resonance, and the remaining are closer to resonance. The option to decrease the module voltage down to 600V, increases the number of required modules per arm from 12 to 15, which requires to balance the losses of the LLCs and the grid-side stages.
Keywords: Multilevel converters; Resonant converter; High voltage power converters; ZVS Converters; Combination MMC LLC

Effect of vitamin D deficiency on depressive symptoms in child and adolescent psychiatric patients: results of a randomized controlled trial - Libuda, Lars; Timmesfeld, Nina; Antel, Jochen; Hirtz, Raphael; Bauer, Jens; Führer, Dagmar; Zwanziger, Denise; Öztürk, Dana; Langenbach, Gina; Hahn, Denise; Ring, Stefanie; Peters, Triinu; et al. (European Journal of Nutrition)
Abstract Purpose While observational studies revealed inverse associations between serum vitamin D levels [25(OH)D] and depression, randomized controlled trials (RCT) in children and adolescents are lacking. This RCT examined the effect of an untreated vitamin D deficiency compared to an immediate vitamin D 3 supplementation on depression scores in children and adolescents during standard day and in-patient psychiatric treatment. Methods Patients with vitamin D deficiency [25(OH)D ≤ 30 nmol/l] and at least mild depression [Beck Depression Inventory II (BDI-II) > 13] ( n = 113) were 1:1 randomized into verum (VG; 2640 IU vitamin D 3 /d) or placebo group (PG) in a double-blind manner. During the intervention period of 28 days, both groups additionally received treatment as usual. BDI-II scores were assessed as primary outcome, DISYPS-II (Diagnostic System for Mental Disorders in Childhood and Adolescence, Self- and Parent Rating) and serum total 25(OH)D were secondary outcomes. Results At admission, 49.3% of the screened patients ( n = 280) had vitamin D deficiency. Although the intervention led to a higher increase of 25(OH)D levels in the VG than in the PG (treatment difference: + 14 ng/ml; 95% CI 4.86–23.77; p = 0.003), the change in BDI-II scores did not differ (+ 1.3; 95% CI − 2.22 to 4.81; p = 0.466). In contrast, DISYPS parental ratings revealed pronounced improvements of depressive symptoms in the VG (− 0.68; 95% CI − 1.23 to − 0.13; p = 0.016). Conclusion Whereas this study failed to show a vitamin D supplementation effect on self-rated depression in adolescent in- or daycare patients, parents reported less depressive symptoms in VG at the end of our study. Future trials should consider clinician-rated depressive symptoms as primary outcome. Trial registration “German Clinical Trials Register” ( https://www.drks.de ), registration number: DRKS00009758

Evaluation of Metabolic Profiles of Patients with Anorexia Nervosa at Inpatient Admission, Short- and Long-Term Weight Regain—Descriptive and Pattern Analysis - Föcker, Manuel; Cecil, Alexander; Prehn, Cornelia; Adamski, Jerzy; Albrecht, Muriel; Adams, Frederike; Hinney, Anke; Libuda, Lars; Bühlmeier, Judith; Hebebrand, Johannes; Peters, Triinu; Antel, Jochen (Metabolites)
Acute anorexia nervosa (AN) constitutes an extreme physiological state. We aimed to detect state related metabolic alterations during inpatient admission and upon short- and long-term weight regain. In addition, we tested the hypothesis that metabolite concentrations adapt to those of healthy controls (HC) after long-term weight regain. Thirty-five female adolescents with AN and 25 female HC were recruited. Based on a targeted approach 187 metabolite concentrations were detected at inpatient admission (T0), after short-term weight recovery (T1; half of target-weight) and close to target weight (T2). Pattern hunter and time course analysis were performed. The highest number of significant differences in metabolite concentrations (N = 32) were observed between HC and T1. According to the detected main pattern, metabolite concentrations at T2 became more similar to those of HC. The course of single metabolite concentrations (e.g., glutamic acid) revealed different metabolic subtypes within the study sample. Patients with AN after short-term weight regain are in a greater “metabolic imbalance” than at starvation. After long-term weight regain, patients reach a metabolite profile similar to HC. Our results might be confounded by different metabolic subtypes of patients with AN.

Short-term effects of carbohydrates differing in glycemic index (GI) consumed at lunch on children’s cognitive function in a randomized crossover study - Jansen, Kathrin; Tempes, Jana; Drozdowska, Alina; Gutmann, Maike; Falkenstein, Michael; Buyken, Anette; Libuda, Lars; Rudolf, Henrik; Lücke, Thomas; Kersting, Mathilde (European Journal of Clinical Nutrition)

Physical activity and health promotion for nursing staff in elderly care: a study protocol for a randomised controlled trial - Otto, Ann-Kathrin; Pietschmann, Juliane; Appelles, Luisa-Marie; Bebenek, Michael; Bischoff, Laura L; Hildebrand, Claudia; Johnen, Bettina; Jöllenbeck, Thomas; Kemmler, Wolfgang; Klotzbier, Thomas; Korbus, Heide; Rudisch, Julian; et al. (BMJ Open)
Introduction Nursing staff is burdened by high workload and stress. Furthermore, heavy lifting, as well as transferring nursing home residents, cause lumbar tissue damage and back pain. Exercise intervention studies to reduce work-related problems are rare and the evidence for efficacy of studies among nurses is limited. Studies including targeted analysis of requirements are necessary to generate effective recommendations and tailored interventions for health promotion programmes. The purpose of this multicentred intervention study is to identify work-related problems, to implement health promotion programmes and to evaluate their effectiveness. Methods and analysis A randomised controlled trial will be conducted, including a total of 48 nursing home facilities in eight regions of Germany with an estimated sample size of 700 nurses. Standardised ergonomics and posture training (10 weeks, once a week for 20–30 min) and subsequently, back-fitness training (12 weeks, once a week for 45–60 min) will be administered. Following the implementation of standardised health promotion programmes, further demand-oriented interventions can be implemented. The perceived exposure to work-related demands, work-related pain in different parts of the body, health-related quality of life, perceived stress, work-related patterns of behaviour and experience, presentism behaviour, work environment as well as general needs and barriers to health promotion, will be assessed at baseline (pre-test), at 10 weeks (post-test, after ergonomics training), at 22 weeks (post-test, after back-fitness training) and at 34 weeks of the programme (follow-up). Ethics and dissemination The study was reviewed and approved by the local ethics committee of the University of Hamburg (AZ: 2018_168). The results of the study will be published in open-access and international journals. Furthermore, the results will be presented in the participating nursing homes and at national and international conferences. Trial registration number DRKS.de (DRKS00015241).
Keywords: General Medicine

1. Sonntag nach Weihnachten 27.12.2020. Lukas 2,(22-24)25-38(39-40): Missionarische Spiritualität - Schroeter-Wittke, Harald; Kirsner, Inge (Predigtstudien III/1)

Kommunale Planung für Senior*innen bis 2025. Fortschreibung des Altenhilfeplans aus dem Jahr 2013

Auswirkungen der digitalen Flexibilisierung des Fertigungsortes auf die Verteilung der Besteuerungsrechte – Ergebnisse von Modellrechnungen zum 3D-Druck-Verfahren - Mair, Christina; Scheffler, Wolfram; Senger, Isabell; Sureth-Sloane, Caren (Steuer und Wirtschaft)

Psychische Auffälligkeiten bei Kindern und Jugendlichen, für die das Jugendamt in Anspruch genommen wurde - Wagenknecht, Inga; Meier-Gräwe, Uta (Praxis der Kinderpsychologie und Kinderpsychiatrie)
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics

Golf spielen gegen die Vergesslichkeit: Effekte des Erlernens der Sportart auf das Default Mode Netzwerk des Gehirns - Ströhlein, Julia Kristin; Vieluf, Solveig; van den Bongard, Franziska; Gölz, Christian Johannes; Reinsberger, Claus (B&G Bewegungstherapie und Gesundheitssport)
Zusammenfassung Einleitung Im Rahmen der Demenz vom Alzheimer-Typ (DAT) zeigt sich eine gestörte neuronale Netzwerkorganisation, welche sich unter anderem auch im Default Mode Netzwerk (DMN) widerspiegelt. Multimodale Interventionen, wie zum Beispiel Golf, können einen positiven Einfluss auf die funktionelle Integrität der Netzwerke haben. Methodik Im Rahmen einer Pilotstudie wurde der Einfluss des Erlernens der Sportart Golf bei sieben älteren Menschen (> 60 Jahre) mit subjektiven Gedächtnisbeschwerden auf die funktionelle Konnektivität des DMN untersucht. Die Probanden haben 22 Wochen unter Anleitung eines professionellen Golftrainers dreimal wöchentlich je 60 min trainiert. Vor (Messzeitpunkt 0, MZP0) und nach der Intervention (Messzeitpunkt 1, MZP1) wurde eine Elektroenzephalografie (EEG)-Messung unter Ruhebedingungen (resting-state) durchgeführt. Die EEG-Daten wurden mit einem Magnetresonanztomographie-Template koregistriert. Die Konnektivitätsanalyse wurde in 15 Regionen des DMN durchgeführt und im Längsschnitt verglichen. Dabei wurden die Frequenzbänder beta (14–29 Hz) und theta (5–7 Hz) berücksichtigt. Ergebnisse Nach der Intervention wurde eine höhere funktionelle Konnektivität im gesamten DMN bei 5 / 7 Teilnehmenden im beta Frequenzband bzw. bei 6 / 7 Probanden im theta Frequenzband zu MZP1 im Vergleich zu MZP0 gemessen. Im anterioren DMN war bei allen Probanden und Probandinnen die funktionelle Konnektivität im beta Frequenzband zu MZP1 im Vergleich zu MZP 0 höher, während sie im theta-Band bei 6 von 7 Teilnehmenden niedriger war. Im posterioren DMN war bei 6 von 7 (beta), bzw. 5 von 7 (theta) Probanden und Probandinnen die funktionelle Konnektivität zu MZP1 höher als zu MZP0. Spearman-Korrelationsanalysen zeigen zudem einen Zusammenhang zwischen der Teilnahmehäufigkeit und der prozentualen Veränderung der funktionellen Konnektivität im gesamten DMN des beta Frequenzbandes (r = 0,786, p = 0,036) und im anterioren DMN des theta Frequenzbandes (r = –0,821, p = 0,023). Fazit Auf Basis der vorliegenden Daten lässt sich vermuten, dass das Erlernen der Sportart Golf einen Einfluss auf das DMN haben könnte. Die Ergebnisse bilden die Grundlage für die Planung einer Studie mit einer größeren Kohorte und randomisierten kontrollierten Design.

Healthy subjects with lax knees use less knee flexion rather than muscle control to limit anterior tibia translation during landing - Keizer, Michèle N. J.; Hijmans, Juha M.; Gokeler, Alli; Benjaminse, Anne; Otten, Egbert (Journal of Experimental Orthopaedics)
Abstract Purpose It has been reported that there is no correlation between anterior tibia translation (ATT) in passive and dynamic situations. Passive ATT (ATTp) may be different to dynamic ATT (ATTd) due to muscle activation patterns. This study aimed to investigate whether muscle activation during jumping can control ATT in healthy participants. Methods ATTp of twenty-one healthy participants was measured using a KT-1000 arthrometer. All participants performed single leg hops for distance during which ATTd, knee flexion angles and knee flexion moments were measured using a 3D motion capture system. During both tests, sEMG signals were recorded. Results A negative correlation was found between ATTp and the maximal ATTd (r = − 0.47, p = 0.028). An N-Way ANOVA showed that larger semitendinosus activity was seen when ATTd was larger, while less biceps femoris activity and rectus femoris activity were seen. Moreover, larger knee extension moment, knee flexion angle and ground reaction force in the anterior-posterior direction were seen when ATTd was larger. Conclusion Participants with more ATTp showed smaller ATTd during jump landing. Muscle activation did not contribute to reduce ATTd during impact of a jump-landing at the observed knee angles. However, subjects with large ATTp landed with less knee flexion and consequently showed less ATTd. The results of this study give information on how healthy people control knee laxity during jump-landing. Level of evidence III
Keywords: Orthopedics and Sports Medicine

Gemeinsam Forschung gestalten. Handreichung zu partizipativer Forschung - Lutz, Katharina; Offergeld, Jana; Freymuth, Nina; Arp, Anna Liza

Parameterized complexity of abduction in Schaefer’s framework - Mahmood, Yasir; Meier, Arne; Schmidt, Johannes (Journal of Logic and Computation)
Abstract Abductive reasoning is a non-monotonic formalism stemming from the work of Peirce. It describes the process of deriving the most plausible explanations of known facts. Considering the positive version, asking for sets of variables as explanations, we study, besides the problem of wether there exists a set of explanations, two explanation size limited variants of this reasoning problem (less than or equal to, and equal to a given size bound). In this paper, we present a thorough two-dimensional classification of these problems: the first dimension is regarding the parameterized complexity under a wealth of different parameterizations, and the second dimension spans through all possible Boolean fragments of these problems in Schaefer’s constraint satisfaction framework with co-clones (T. J. Schaefer. The complexity of satisfiability problems. In Proceedings of the 10th Annual ACM Symposium on Theory of Computing, May 1–3, 1978, San Diego, California, USA, R.J. Lipton, W.A. Burkhard, W.J. Savitch, E.P. Friedman, A.V. Aho eds, pp. 216–226. ACM, 1978). Thereby, we almost complete the parameterized complexity classification program initiated by Fellows et al. (The parameterized complexity of abduction. In Proceedings of the Twenty-Sixth AAAI Conference on Articial Intelligence, July 22–26, 2012, Toronto, Ontario, Canada, J. Homann, B. Selman eds. AAAI Press, 2012), partially building on the results by Nordh and Zanuttini (What makes propositional abduction tractable. Artificial Intelligence, 172, 1245–1284, 2008). In this process, we outline a fine-grained analysis of the inherent parameterized intractability of these problems and pinpoint their FPT parts. As the standard algebraic approach is not applicable to our problems, we develop an alternative method that makes the algebraic tools partially available again.
Keywords: Logic; Hardware and Architecture; Arts and Humanities (miscellaneous); Software; Theoretical Computer Science

NFDI4Culture - Consortium for research data on material and immaterial cultural heritage - Altenhöner, Reinhard; Blümel, Ina; Boehm, Franziska; Bove, Jens; Bicher, Katrin; Bracht, Christian; Brand, Ortrun; Dieckmann, Lisa; Effinger, Maria; Hagener, Malte; Hammes, Andrea; Heller, Lambert; et al. (Research Ideas and Outcomes)
Digital data on tangible and intangible cultural assets is an essential part of daily life, communication and experience. It has a lasting influence on the perception of cultural identity as well as on the interactions between research, the cultural economy and society. Throughout the last three decades, many cultural heritage institutions have contributed a wealth of digital representations of cultural assets (2D digital reproductions of paintings, sheet music, 3D digital models of sculptures, monuments, rooms, buildings), audio-visual data (music, film, stage performances), and procedural research data such as encoding and annotation formats. The long-term preservation and FAIR availability of research data from the cultural heritage domain is fundamentally important, not only for future academic success in the humanities but also for the cultural identity of individuals and society as a whole. Up to now, no coordinated effort for professional research data management on a national level exists in Germany. NFDI4Culture aims to fill this gap and create a user-centered, research-driven infrastructure that will cover a broad range of research domains from musicology, art history and architecture to performance, theatre, film, and media studies. The research landscape addressed by the consortium is characterized by strong institutional differentiation. Research units in the consortium's community of interest comprise university institutes, art colleges, academies, galleries, libraries, archives and museums. This diverse landscape is also characterized by an abundance of research objects, methodologies and a great potential for data-driven research. In a unique effort carried out by the applicant and co-applicants of this proposal and ten academic societies, this community is interconnected for the first time through a federated approach that is ideally suited to the needs of the participating researchers. To promote collaboration within the NFDI, to share knowledge and technology and to provide extensive support for its users have been the guiding principles of the consortium from the beginning and will be at the heart of all workflows and decision-making processes. Thanks to these principles, NFDI4Culture has gathered strong support ranging from individual researchers to high-level cultural heritage organizations such as the UNESCO, the International Council of Museums, the Open Knowledge Foundation and Wikimedia. On this basis, NFDI4Culture will take innovative measures that promote a cultural change towards a more reflective and sustainable handling of research data and at the same time boost qualification and professionalization in data-driven research in the domain of cultural heritage. This will create a long-lasting impact on science, cultural economy and society as a whole.
Keywords: Research Data Management

Analysis of the Characteristic Flow Areas for Erdmenger-Elements to Predict the Throughput-Pressure Behavior of Co-Rotating Twin Screw Extruders by Using 3D FEM Simulation - Schöppner, Volker; Sporkmann, F. (35th International Conference of the Polymer Processing Society (PPS))

Vorausschau und Technologieplanung. 15. Symposium für Vorausschau und Technologieplanung, Heinz Nixdorf Institut, 21. und 22. November 2019 - Gausemeier, Jürgen

Analyse sicherheitskritischer Software für RISC-V Prozessoren - Adelt, Peer; Koppelmann, Bastian; Müller, Wolfgang; Scheytt, Christoph (MBMV 2019-22.Workshop Methoden und Beschreibungssprachen zur Modellierung und Verifikation von Schaltungen und Systemen (MBMV 2019))
In diesem Artikel stellen wir eine Methode zur nicht-invasiven dynamischen Speicher- und IO-Analyse mit QEMU für sicherheitskritische eingebettete Software für die RISC-V Befehlssatzarchitektur vor. Die Implementierung basiert auf einer Erweiterung des Tiny Code Generator (TCG) des quelloffenen CPU-Emulators QEMU um die dynamische Identifikation von Zugriffen auf Datenspeicher sowie auf an die CPU angeschlossene IO-Geräte. Wir demonstrieren die Funktionalität der Methode anhand eines Versuchsaufbaus, bei dem eine Schließsystemkontrolle mittels serieller UART-Schnittstelle an einen RISC-V-Prozessor angebunden ist. Dieses Szenario zeigt, dass ein unberechtigter Zugriff auf die UART-Schnittstelle frühzeitig aufgedeckt und ein Angriff auf eine Zugangskontrolle somit endeckt werden kann.

Influence of precursor concentration on spray and particle formation in flame spray pyrolysis - Bieber, M.; Tischendorf, R.; Reddemann, M.; Schmid, H.-J.; Kneer, R.
Liquid atomization is expected to be a key process in Flame Spray Pyrolysis, as it determines the primary droplet size and velocity distribution, which represent initial conditions for flame shape and temperature field. A well-defined manipulation of atomization may be achieved by variation of nozzle geometry, injection parameter or fluid properties. However, change of fluid properties, e.g. varying solvents or increasing the precursor concentration, also influences the final particle properties. In this work, the influence of precursor concentration on fluid properties, spray and particle formation in Flame Spray Pyrolysis is experimentally investigated. High-speed shadowgraphy and Phase-Doppler measurements are conducted in a semi-closed combustion chamber with a well-defined burner geometry (SpraySyn burner) that is based on a coaxial atomization principle. By adding precursor to the flammable solvent, resulting spray characteristics, flame shape and appearance are changed in color, shape and mean droplet size distribution. Compared to resulting mean droplet sizes of pure solvent mixtures (D32, 22 μm), mean droplet sizes in the center of the precursor flame at 30 mm above the burner are generally smaller (D32, 18 μm). Persisting high share of small droplets in the droplet size distribution are presented, that presumably origin from an accumulation of metal organic precursor at the droplet surface during combustion, that acts as a diffusive barrier for high volatility solvent and thus reduces droplet evaporation. Sufficiently high above the nozzle exit, increasing the precursor concentration does not affect the radial distribution of mean droplet sizes but leads to increased mean particle sizes. More precursor presumably leads to higher concentrations of prime particles in the flame, thus probability of particle collusion and agglomeration. High-speed imaging at nozzle exit revealed random fluctuations of initial jet diameter, paired with jet axis shifting around 1000 Hz. These superposed fluctuations determine the initial conditions for atomization, induce pulsations in the flame and thus initiate the entire chain of the particle synthesis process.
Keywords: FSP; nanoparticle synthesis; in situ measurements

Age and time trends in sugar intake among children and adolescents: results from the DONALD study - Perrar, Ines; Schmitting, Sarah; Della Corte, Karen W.; Buyken, Anette; Alexy, Ute (European Journal of Nutrition)

Is there a soft drink vs. alcohol seesaw? A cross-sectional analysis of dietary data in the Australian Health Survey 2011–12 - Wong, Tommy H. T.; Buyken, Anette; Brand-Miller, Jennie C.; Louie, Jimmy Chun Yu (European Journal of Nutrition)

Dietary sugars and cardiometabolic risk factors: a network meta-analysis on isocaloric substitution interventions - Schwingshackl, Lukas; Neuenschwander, Manuela; Hoffmann, Georg; Buyken, Anette; Schlesinger, Sabrina (The American Journal of Clinical Nutrition)
ABSTRACT Background There is controversy on the relevance of dietary sugar intake for cardiometabolic health. Objective The aim of this network meta-analysis (NMA) was to assess how isocaloric substitutions of dietary sugar with other carbohydrates affect cardiometabolic risk factors, comparing different intervention studies. Methods We included randomized controlled trials (RCTs) investigating the isocaloric effect of substituting dietary sugars (fructose, glucose, sucrose) with other sugars or starch on cardiometabolic risk markers, including LDL cholesterol, triacylglycerol (TG), fasting glucose (FG), glycated hemoglobin (HbA1c), insulin resistance (HOMA-IR), uric acid, C-reactive protein (CRP), alanine transaminase (ALT), aspartate transaminase (AST), and liver fat content. To identify the most beneficial intervention for each outcome, random-effects NMA was conducted by calculating pooled mean differences (MDs) with 95% CIs, and by ranking the surface under the cumulative ranking curves (SUCRAs). The certainty of evidence was evaluated using the Confidence In Network Meta-Analysis tool. Results Thirty-eight RCTs, including 1383 participants, were identified. A reduction in LDL-cholesterol concentrations was shown for the exchange of sucrose with starch (MD: −0.23 mmol/L; 95% CI: −0.38, −0.07 mmol/L) or fructose with starch (MD: −0.22 mmol/L; 95% CI: −0.39, −0.05 mmol/L; SUCRAstarch: 98%). FG concentrations were also lower for the exchange of sucrose with starch (MD: −0.14 mmol/L; 95% CI: −0.29, 0.01 mmol/L; SUCRAstarch: 91%). Replacing fructose with an equivalent energy amount of glucose reduced HOMA-IR (MD: −0.36; 95% CI: −0.71, −0.02; SUCRAglucose: 74%) and uric acid (MD: −23.77 µmol/L; 95% CI: −44.21, −3.32 µmol/L; SUCRAglucose: 93%). The certainty of evidence was rated very low to moderate. No significant effects were observed for TG, HbA1c, CRP, ALT, and AST. Conclusions Our findings indicate that substitution of sucrose and fructose with starch yielded lower LDL cholesterol. Insulin resistance and uric acid concentrations were beneficially affected by replacement of fructose with glucose. Our findings are limited by the very low to moderate certainty of evidence. This review was registered at www.crd.york.ac.uk/prospero as CRD42018080297.

Time and Age Trends in Free Sugar Intake from Food Groups among Children and Adolescents between 1985 and 2016 - Perrar, Ines; Schadow, Alena M.; Schmitting, Sarah; Buyken, Anette; Alexy, Ute (Nutrients)
Trend analyses suggest that free sugar (FS) intake—while still exceeding 10%E—has decreased among German children and adolescents since 2005, yet that intakes may shift from sugars naturally occurring in foods to added sugars as children age. Thus, we analysed time and age trends in FS intake (%E) from food groups among 3–18 year-olds (1985–2016) using 10,761 3-day dietary records from 1312 DONALD participants (660 boys, 652 girls) by use of polynomial mixed-effects regression models. Among girls, FS from sugar & sweets decreased from 1985 to 2016 (linear trend p < 0.0001), but not among boys (p > 0.05). In the total sample, FS intake from juices increased until 2000 and decreased since 2005 (linear, quadratic trend p < 0.0001). FS from sugar sweetened beverages (SSB) decreased non-linearly from 1985 to 2016 (girls: linear, quadratic, cubic trend p < 0.0001; boys: linear, quadratic, cubic trend p < 0.02). Younger children consumed more FS from juices than older ones, who had a higher FS intake from SSB. FS intake from sugar & sweets increased until early adolescence and decreased afterwards. Since sugar & sweets represent the main source of FS intake and the source with the least pronounced decline in intake, public health measures should focus on these products.

Assessing causal links between metabolic traits, inflammation and schizophrenia: a univariable and multivariable, bidirectional Mendelian-randomization study - Lin, Bochao D; Alkema, Anne; Peters, Triinu; Zinkstok, Janneke; Libuda, Lars; Hebebrand, Johannes; Antel, Jochen; Hinney, Anke; Cahn, Wiepke; Adan, Roger; Luykx, Jurjen J (International Journal of Epidemiology)
Abstract Background Blood immunoreactive biomarkers, such as C-reactive protein (CRP), and metabolic abnormalities have been associated with schizophrenia. Studies comprehensively and bidirectionally probing possible causal links between such blood constituents and liability to schizophrenia are lacking. Methods To disentangle putative causal links between CRP blood levels and schizophrenia in both directions, we conducted multiple univariable Mendelian-randomization (MR) analyses, ranging from fixed-effect to inverse variance-weighted (IVW), weighted-median, MR Egger and generalized summary-data-based Mendelian-randomization (GSMR) models. To prioritize metabolic risk factors for schizophrenia, a novel multivariable approach was applied: multivariable Mendelian-randomization–Bayesian model averaging (MR-BMA). Results All forward univariable MR analyses consistently showed that CRP has a protective effect on schizophrenia, whereas reverse MR analyses consistently suggested absent causal effects of schizophrenia liability on CRP blood levels. Using MR-BMA, as the top protective factors for schizophrenia we prioritized leucine and as the prime risk-factor triglycerides in medium very-low-density lipoprotein (VLDL). The five best-performing MR-BMA models provided one additional risk factor: triglycerides in large VLDL; and two additional protective factors: citrate and lactate. Conclusions Our results add to a growing body of literature hinting at metabolic changes—in particular of triglycerides—independently of medication status in schizophrenia. We also highlight the absent effects of genetic liability to schizophrenia on CRP levels.

Effects of LC-PUFA supply via complementary food on infant development—a food based intervention (RCT) embedded in a total diet concept - Kalhoff, Hermann; Mesch, Christina M.; Stimming, Madlen; Israel, Andreas; Spitzer, Christoph; Beganovic, Latifa; Perez, Rocio Estella; Koletzko, Berthold; Warschburger, Petra; Kersting, Mathilde; Libuda, Lars (European Journal of Clinical Nutrition)

Verbraucherbildung als Bildung für Lebensführung - Schlegel-Matthies, Kirsten (Verbraucherbildung: Ein weiter Weg zum mündigen Verbraucher)

Haushaltsbezogene Bildung – quo vadis? Daseinsvorsorge und Lebensführung im Wandel - Schlegel-Matthies, Kirsten (Haushalt in Bildung & Forschung)
Der Beitrag geht der Frage nach, wie haushaltsbezogene Bildung als Ernährungs- und Verbraucherbildung umgesetzt werden kann, damit Jugendliche selbstbestimmt und verantwortlich ihre individuellen Vorstellungen von einem „guten“ und „gelingenden“ Leben umsetzen können. Die Auseinandersetzung mit dem Zusammenwirken von gesellschaftlicher Lebensweise, privater Lebensführung und individuellen Lebensstilen erweist sich dabei als bedeutsam.

Dietary Glycemic Index and Load and the Risk of Type 2 Diabetes: A Systematic Review and Updated Meta-Analyses of Prospective Cohort Studies - Livesey, Geoffrey; Taylor, Richard; Livesey, Helen F.; Buyken, Anette; Jenkins, David J. A.; Augustin, Livia S. A.; Sievenpiper, John L.; Barclay, Alan W.; Liu, Simin; Wolever, Thomas M. S.; Willett, Walter C.; Brighenti, Furio; et al. (Nutrients)
Published meta-analyses indicate significant but inconsistent incident type-2 diabetes (T2D)-dietary glycemic index (GI) and glycemic load (GL) risk ratios or risk relations (RR). It is now over a decade ago that a published meta-analysis used a predefined standard to identify valid studies. Considering valid studies only, and using random effects dose–response meta-analysis (DRM) while withdrawing spurious results (p < 0.05), we ascertained whether these relations would support nutrition guidance, specifically for an RR > 1.20 with a lower 95% confidence limit >1.10 across typical intakes (approximately 10th to 90th percentiles of population intakes). The combined T2D–GI RR was 1.27 (1.15–1.40) (p < 0.001, n = 10 studies) per 10 units GI, while that for the T2D–GL RR was 1.26 (1.15–1.37) (p < 0.001, n = 15) per 80 g/d GL in a 2000 kcal (8400 kJ) diet. The corresponding global DRM using restricted cubic splines were 1.87 (1.56–2.25) (p < 0.001, n = 10) and 1.89 (1.66–2.16) (p < 0.001, n = 15) from 47.6 to 76.1 units GI and 73 to 257 g/d GL in a 2000 kcal diet, respectively. In conclusion, among adults initially in good health, diets higher in GI or GL were robustly associated with incident T2D. Together with mechanistic and other data, this supports that consideration should be given to these dietary risk factors in nutrition advice. Concerning the public health relevance at the global level, our evidence indicates that GI and GL are substantial food markers predicting the development of T2D worldwide, for persons of European ancestry and of East Asian ancestry.

Dietary Glycemic Index and Load and the Risk of Type 2 Diabetes: Assessment of Causal Relations - Livesey, Geoffrey; Taylor, Richard; Livesey, Helen F.; Buyken, Anette; Jenkins, David J. A.; Augustin, Livia S. A.; Sievenpiper, John L.; Barclay, Alan W.; Liu, Simin; Wolever, Thomas M. S.; Willett, Walter C.; Brighenti, Furio; et al. (Nutrients)
While dietary factors are important modifiable risk factors for type 2 diabetes (T2D), the causal role of carbohydrate quality in nutrition remains controversial. Dietary glycemic index (GI) and glycemic load (GL) have been examined in relation to the risk of T2D in multiple prospective cohort studies. Previous meta-analyses indicate significant relations but consideration of causality has been minimal. Here, the results of our recent meta-analyses of prospective cohort studies of 4 to 26-y follow-up are interpreted in the context of the nine Bradford-Hill criteria for causality, that is: (1) Strength of Association, (2) Consistency, (3) Specificity, (4) Temporality, (5) Biological Gradient, (6) Plausibility, (7) Experimental evidence, (8) Analogy, and (9) Coherence. These criteria necessitated referral to a body of literature wider than prospective cohort studies alone, especially in criteria 6 to 9. In this analysis, all nine of the Hill’s criteria were met for GI and GL indicating that we can be confident of a role for GI and GL as causal factors contributing to incident T2D. In addition, neither dietary fiber nor cereal fiber nor wholegrain were found to be reliable or effective surrogate measures of GI or GL. Finally, our cost–benefit analysis suggests food and nutrition advice favors lower GI or GL and would produce significant potential cost savings in national healthcare budgets. The high confidence in causal associations for incident T2D is sufficient to consider inclusion of GI and GL in food and nutrient-based recommendations.

Developmental trajectories of body mass index from childhood into late adolescence and subsequent late adolescence–young adulthood cardiometabolic risk markers - Oluwagbemigun, Kolade; Buyken, Anette; Alexy, Ute; Schmid, Matthias; Herder, Christian; Nöthlings, Ute (Cardiovascular Diabetology)

DNA origami directed 3D nanoparticle superlattice via electrostatic assembly. - Julin, S; Korpi, A; Shen, B; Liljeström, V; Ikkala, O; Keller, Adrian; Linko, V; Kostiainen, MA (Nanoscale)

Typisierung und Strukturierung digitaler Plattformen im Kontext Business-to-Business - Wortmann, Fabio; Ellermann, Kai Fabian; Kühn, Arno; Dumitrescu, Roman (Vorausschau und Technologieplanung, 15. Symposium für Vorausschau und Technologieplanung, 21.-22. November 2019, Berlin)

The 31st ACM Symposium on Parallelism in Algorithms and Architectures, SPAA 2019, Phoenix, AZ, USA, June 22-24, 2019

Analyse der Veränderung der zwischenstaatlichen Gewinnaufteilung bei Einführung einer standardisierten Gewinnverteilungsmethode am Beispiel des Einsatzes von 3D-Druckern - Mair, Christina; Scheffler, Wolfram; Senger, Isabell; Sureth-Sloane, Caren

Rendering of Complex Heterogenous Scenes using Progressive Blue Surfels - Brandt, Sascha; Jähn, Claudius; Fischer, Matthias; Meyer auf der Heide, Friedhelm (arXiv:1904.08225)
We present a technique for rendering highly complex 3D scenes in real-time by generating uniformly distributed points on the scene's visible surfaces. The technique is applicable to a wide range of scene types, like scenes directly based on complex and detailed CAD data consisting of billions of polygons (in contrast to scenes handcrafted solely for visualization). This allows to visualize such scenes smoothly even in VR on a HMD with good image quality, while maintaining the necessary frame-rates. In contrast to other point based rendering methods, we place points in an approximated blue noise distribution only on visible surfaces and store them in a highly GPU efficient data structure, allowing to progressively refine the number of rendered points to maximize the image quality for a given target frame rate. Our evaluation shows that scenes consisting of a high amount of polygons can be rendered with interactive frame rates with good visual quality on standard hardware.

Numerical Simulation of Forced Convection in a Microchannel with Realistic Roughness of 3D Printed Surface - Manavi, Seyed Alborz; Kenig, Eugeny (Computer Aided Chemical Engineering)

Combining Verifiers in Conditional Model Checking via Reducers - Beyer, Dirk; Jakobs, Marie-Christine; Lemberger, Thomas; Wehrheim, Heike (Software Engineering and Software Management (SE/SWM 2019), Stuttgart, Germany, February 18-22, 2019)

Testing Balancedness of ML Algorithms - Sharma, Arnab; Wehrheim, Heike (Software Engineering and Software Management, {SE/SWM} 2019, Stuttgart, Germany, February 18-22, 2019)

Plastic droplet welding: bond strength between plastic freeforming structures and continuous fiber-reinforced thermoplastic composites - Moritzer, Elmar; Hirsch, André; Heim, H.P.; Cherif, C.; Truemper, W. (Welding in the World)
Plastic freeforming (PF) is an additive-manufacturing process for producing three-dimensional plastic parts based on 3D CAD data by applying plastic droplets in layers. This process is used to produce customer-specific and complex geometries (prototypes and small series) on organic sheets. A comparable serial process is the injection of a second component onto organic sheets by injection molding. A sufficient bond between the PF structure and the organic sheets is of particular importance for each application. If this is not guaranteed, the composite system cannot withstand the mechanical load and fails. The force exerted on the system can no longer be transmitted between the PF structure and the organic sheet. The organic sheet is made of glass fiber-reinforced polypropylene (PP). The connection between the organic sheet and the PF structure is achieved by welding the molten polymer droplets and the surface of the organic sheet. The PF structures are made of PP to ensure sufficient compatibility with regard to the weldability of the components. The processing of PP in the PF process is a challenge because PP is a semicrystalline material. The shrinkage of semi-crystalline materials is significantly higher compared to amorphous materials. Due to the layered structure of the components, the shrinkage of the individual layers results in undesired warpage. The adhesive strength between the organic sheet and the PF structure is investigated by determining the bending strength in the 3-point bending test. The investigations include an optimization of the process parameters to maximize the adhesive strength. The experimental investigations show that an increase of the nozzle and build chamber temperature leads to a higher adhesive strength. In further investigations, the temperature of the nozzle shows no significant influence on the surface temperature despite the expected heat radiation. The surface temperature is almost only dependent on the temperature of the build chamber.

Vitamin D and the Risk of Depression: A Causal Relationship? Findings from a Mendelian Randomization Study - Libuda, Lars; Laabs, Björn-Hergen; Ludwig, Christine; Bühlmeier, Judith; Antel, Jochen; Hinney, Anke; Naaresh, Roaa; Föcker, Manuel; Hebebrand, Johannes; König, Inke R.; Peters, Triinu (Nutrients)
While observational studies show an association between 25(OH)vitamin D concentrations and depressive symptoms, intervention studies, which examine the preventive effects of vitamin D supplementation on the development of depression, are lacking. To estimate the role of lowered 25(OH)vitamin D concentrations in the etiology of depressive disorders, we conducted a two-sample Mendelian randomization (MR) study on depression, i.e., “depressive symptoms” (DS, n = 161,460) and “broad depression” (BD, n = 113,769 cases and 208,811 controls). Six single nucleotide polymorphisms (SNPs), which were genome-wide significantly associated with 25(OH)vitamin D concentrations in 79,366 subjects from the SUNLIGHT genome-wide association study (GWAS), were used as an instrumental variable. None of the six SNPs was associated with DS or BD (all p > 0.05). MR analysis revealed no causal effects of 25(OH)vitamin D concentration, either on DS (inverse variance weighted (IVW); b = 0.025, SE = 0.038, p = 0.52) or on BD (IVW; b = 0.020, SE = 0.012, p = 0.10). Sensitivity analyses confirmed that 25(OH)vitamin D concentrations were not significantly associated with DS or BD. The findings from this MR study indicate no causal relationship between vitamin D concentrations and depressive symptoms, or broad depression. Conflicting findings from observational studies might have resulted from residual confounding or reverse causation.

Risk factors for a low weight gain in the early stage of adolescent anorexia nervosa inpatient treatment: findings from a pilot study - Knoll-Pientka, Nadja; Bühlmeier, Judith; Peters, Triinu; Albrecht, Muriel; Adams, Frederike; Wustrau, Katharina; Teufel, Martin; Hebebrand, Johannes; Föcker, Manuel; Libuda, Lars (Eating and Weight Disorders - Studies on Anorexia, Bulimia and Obesity)

Clinical Trials Required to Assess Potential Benefits and Side Effects of Treatment of Patients With Anorexia Nervosa With Recombinant Human Leptin - Hebebrand, Johannes; Milos, Gabriella; Wabitsch, Martin; Teufel, Martin; Führer, Dagmar; Bühlmeier, Judith; Libuda, Lars; Ludwig, Christine; Antel, Jochen (Frontiers in Psychology)

Mit 3D-Druck umfassende Teilhabe möglich machen - Kruse, Anne; Mummert, Michael (Werkstatt:Dialog)

Posterbeitrag: Didaktisches Konzept und Prototyp eines auf Augmented Reality basierenden virtuellen Vorpraktikums in der Elektrotechnik - Alptekin, Mesut; Temmen, Katrin
Es existieren bisher zahlreiche Studien, die das Potenzial von Augmented Reality (AR) in verschiedenen Bildungsbereichen und seine Auswirkungen auf die Lernenden hinsichtlich ihrer erhöhten Motivation, verbesserter Lernfähigkeit, Konzentration auf das Thema usw. hervorheben. Dabei eignen sich AR-Anwendungen sowohl für den Einsatz in formellen, als auch informellen Lernumgebungen und Bildungsinstitutionen, beginnend mit Kunstkursen in Vorschulen über Biologie, Geschichte, Chemie, Physik etc. in weiterführenden Schulen und Universitäten [1]. Trotz der steigenden Zahl an Studien liegen nur wenigen AR-Anwendungen ein geeignetes didaktisches Konzept zu Grunde. Ferner fehlen allgemeine Studien, die die lernfördernden Eigenschaften von AR im Bereich der Vorbereitung und Begleitung von Laborpraktika untersuchen. Aktuelle Anwendungen erweitern lediglich gedruckte Lerninhalte mit zusätzlichen Links, Videos oder statischen 3D-Modellen oder benötigen spezielle Voraussetzung für die Nutzung der AR-Anwendung [2]. Der vorliegende Beitrag untersucht und konzentriert sich daher auf ein didaktisches Konzept für eine auf mobilen Geräten basierende AR-Anwendung (App) zum Erwerb und zur Vertiefung praktischer Fertigkeiten im Umgang mit elektrotechnischen Laborgeräten und -komponenten. In einer früheren Arbeit wurden die Möglichkeiten und Grenzen der AR-Technologie in der Ingenieurausbildung mit besonderem Fokus auf Laborarbeit untersucht, um häufige Fehler im Designkonzept zu vermeiden. Das didaktische Grundkonzept beruht auf dem „Constructive Alignement“ nach Biggs [3] mit der Definition der drei obligatorischen Schritte: Lernziele, Lehr- / Lernaktivitäten und Prüfungsmethoden. Die Lernziele werden – angelehnt an die modifizierte Bloom-Taxonomie nach Anderson und Krathwohl [4] – weiter konkretisiert, woraus dann im weiteren Schritt mögliche Lehrszenarien in AR gestaltet wurden.
Keywords: Augmented Reality; Laborpraktikum; didaktische Konzepte; Constructive Alignment

Deep eutectic solvents as active media for the preparation of highly conducting 3D free-standing PANI xerogels and their derived N-doped and N-, P-codoped porous carbons - Sánchez-Leija, R.J.; Lopez Salas, Nieves; Fierro, J.L.G.; Gutiérrez, M.C.; Ferrer, M.L.; Mota-Morales, J.D.; Luna-Bárcenas, G.; Monte, F. del (Carbon)
Keywords: General Chemistry; General Materials Science

Anisotropic Water-Mediated Proton Conductivity in Large Iron(II) Metal–Organic Framework Single Crystals for Proton-Exchange Membrane Fuel Cells - Bunzen, Hana; Javed, Ali; Klawinski, Danielle; Lamp, Anton; Grzywa, Maciej; Kalytta-Mewes, Andreas; Tiemann, Michael; von Nidda, Hans-Albrecht Krug; Wagner, Thorsten; Volkmer, Dirk (ACS Applied Nano Materials)
Herein we present a new proton-conducting iron(II) metal–organic framework (MOF) of an unusual structure formed by chains of alternating bistriazolate-p-benzoquinone anions and iron(II) cations with four axially coordinated water molecules. These chains assemble via π–π stacking between the aromatic units to form a three-dimensional grid-like network with channel pores filled with water molecules. The material was structurally characterized by single-crystal XRD analysis, and its water and thermal stability was investigated. The proton conductivity was studied by impedance measurements on needle-like single crystals. A simple but efficient measurement setup consisting of interdigital electrodes was used. The influence of the crystal orientation, temperature, and humidity was investigated. The iron(II)-MOF showed the highest proton conductivity of 3.3·10–3 S cm–1 at 22 °C and 94% relative humidity. Contrary to most known structures, the conductivity in this material is controlled by chemical properties of the pore system rather than by grain boundaries. The presented material is the starting point for further tailoring the proton-conducting properties, independent of morphological features which could find potential applications as membrane materials in proton-exchange membrane fuel cells.

Subcycle Wannier-Stark Localization by Mid-Infrared Bias in Gallium Arsenide - Meier, Torsten; Bühler, Johannes; Schmidt, Christian; Heinrich, Alexander-Cornelius; Allerbeck, Jonas; Podzimski, Reinold; Berghoff, Daniel; Schmidt, Wolf Gero; Reichl, Christian; Wegscheider, Werner; Brida, Daniele; Leitenstorfer, Alfred (XXI International Conference on Ultrafast Phenomena 2018 (UP 2018))
The fundamental interband absorption in gallium arsenide shows a strong blue shift when biased by mid-infrared transients exceeding 10 MV/cm. This subcycle feature is induced by the localization of electronic wavefunctions from 3D to 2D.

Guidelines for post processing oriented design of additive manufactured parts for use in topology optimization - Lammers, Stefan; Tominski, Johannes; Zimmer, Detmar (II International Conference on Simulation for Additive Manufacturing Sim-AM 2019 11-13 September, 2019)
According to ISO / ASTM 52900, additive manufacturing (AM) is defined as "the process of joining materials to make parts from 3D model data, usually layer upon layer, as opposed to conventional manufacturing including subtractive manufacturing technologies and formative manufacturing methodologies” [1]. This results in significant advantages over conventional manufacturing methodologies, such as the production of topologically optimized, complex structures, lower material consumption or shorter product development cycles. In order to be able to use these advantages, the possibilities and restrictions of the processes must be known. In particular, selective laser beam melting (SLM), in which a powdery metallic starting material is melted by means of a laser, requires a sound understanding of the process. For this purpose, design guidelines have been presented in various scientific papers. These design guidelines help to design a component in such a way that it can be manufactured successfully using additive manufacturing. These so-called “AMsuitable design guidelines” can be found among others at Adam, Kranz and Thomas [2,3,4,5]. In contrast to established manufacturing processes, the post-processing of additive components is divided into two steps. First, the AM immanent post processing, such as the removing of the component from the building platform or the removing of the remaining powder. These post-processing steps are in the following referred to “post-processing”. Secondly, the subsequent post-processing steps to improve the component properties, such as milling and turning or a stress-relief annealing. These are referred to as “finishing” and form the focus of this paper. With regard to a successful finishing of additively manufactured components, design guidelines must be taken into account that consider the finishing inherent restrictions and possibilities. In the following, these design guidelines are referred to “finishing suitable”. They can deviate significantly from those of conventionally manufactured components in the case of additively manufactured components. Although there are some investigations that deal with the post-processing of additively manufactured components [6,7], there are hardly any design guidelines that are suitable for finishing [8]. Therefore, knowledge about the finishing of additively manufactured components is based on experimental experience rather than on scientific knowledge. For this reason, design guidelines for a finishing suitable design must be methodically determined and quantified. These quantified design guidelines can be used for an automated design check on complex components like topology optimized geometries.

Toward 3D Integrated Photonics Including Lithium Niobate Thin Films: A Bridge Between Electronics, Radio Frequency, and Optical Technology - Rüsing, Michael; Weigel, Peter O.; Zhao, Jie; Mookherjea, Shayan (IEEE Nanotechnology Magazine)
Keywords: Electrical and Electronic Engineering; Mechanical Engineering

Prinzipien und Strategien der Textgliederung in den Zeitungen des 18. Jahrhunderts – Eine computerbasierte Korpusanalyse - Wille, Manuel (Textgliederungsprinzipien. Ihre Kennzeichnungsformen und Funktionen vom 8. bis 18. Jahrhundert. Akten zum Internationalen Kongress vom 22. bis 24. Juni 2017 an der Universität St. Petersburg)

Textgliederungsprinzipien und Beziehungsgestaltung im Stammbuch von 1559–1878 - Schuster, Britt-Marie (Textgliederungsprinzipien. Ihre Kennzeichnungsformen und Funktionen in Texten vom 8. bis 18. Jahrhundert. Akten zum Internationalen Kongress an der Staatlichen Universität St. Petersburg vom 22. bis 24. Juni 2017)
Keywords: Textsortengeschichte

Unterstützung des Lernens für kritische Situationen: Potenzial von Augmented Reality für die Instandsetzung auf See - Gräßler, Iris; Pottebaum, Jens; Taplick, Patrick; Roesmann, Daniel; Preuß, Daniel (Go-3D 2019 "Mit 3D Richtung Maritim 4.0" - Tagungsband zur Konferenz Go-3D 2019)
Die Instandsetzung von sicherheitskritischen Komponenten durch Besatzungsmitglieder auf See erfordert technische und organisa-torische Unterstützungsmaßnahmen. Zur Instandsetzung kritischer Systeme auf See bietet AR-Technologie erkennbare Potenziale (Räumliche Visualisierung, Kontextualisierung). Zugleich sollen Instandsetzungs-Einsätze im Sinne des informellen arbeits- und einsatzbezogenen Lernens zum Kompetenzerwerb genutzt werden. Dazu wird eine AR-Architektur vorgestellt, die das Lernen im Anwendungsfall ‚Instandsetzung‘ integriert.